2000
DOI: 10.1096/fj.99-0602fje
|View full text |Cite
|
Sign up to set email alerts
|

Lipocortin 1 reduces myocardial ischemia‐reperfusion injury by affecting local leukocyte recruitment

Abstract: We assessed here the effect of the glucocorticoid-regulated protein lipocortin 1 (LC1) in a model of rat myocardial ischemia reperfusion. Treatment of animals with human recombinant LC1 at the end of a 25-min ischemic period significantly reduced the extent of infarct size in the area at risk as measured 2 h later, with approximately 50% inhibition at the highest dose tested of 50 microg per rat (equivalent to 5.4 nmol/kg). The protective effect of LC1 was abolished by protein denaturation and not mimicked by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(119 citation statements)
references
References 58 publications
5
114
0
Order By: Relevance
“…ANXA1 is an important endogenous anti-inflammatory mediator, which is activated in response to cellular or tissue injury [28,29]. In recent years several studies have shown a protective role for ANXA1 and its peptide Ac2-26 in cardiac, mesenteric, cerebral and renal ischemia/reperfusion (I/R) injury [20][21][22][23]30].…”
Section: Discussionmentioning
confidence: 99%
“…ANXA1 is an important endogenous anti-inflammatory mediator, which is activated in response to cellular or tissue injury [28,29]. In recent years several studies have shown a protective role for ANXA1 and its peptide Ac2-26 in cardiac, mesenteric, cerebral and renal ischemia/reperfusion (I/R) injury [20][21][22][23]30].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical procedure has been described [12]. In brief, rats were anaesthetised with urethane (120 mg/kg i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…To distinguish between ischaemic and infarcted tissue, the area at risk was cut into small pieces and incubated with pnitro-blue tetrazolium (NBT, 0.5 mg·ml -1 , 20 min at 37°C). In the presence of intact dehydrogenase enzyme systems (normal myocardium), NBT forms a dark blue formazan, whereas areas of necrosis lack dehydrogenase activity and therefore do not stain [12]. The infarct size (IS), necrotic tissue, as a function of the mass of the area at risk, and the IS as a function of the total left ventricular weight (IS/LV) were calculated according to previous studies [13,14].…”
Section: Methodsmentioning
confidence: 99%
“…Neutralizing antibodies against AnxA1 impaired the anti-inflammatory effects of GCs on carageenininduced paw oedema (Duncan et al, 1993), ischaemia-reperfusion injury (D'Amico et al, 2000) and adjuvant-induced arthritis (Yang et al, 1999). Inflammatory responses of an AnxA1 null mouse strain were exaggerated (Chatterjee et al, 2005;Hannon et al, 2003;Warne et al, 2006;Yang et al, 2004), and cells derived from these mice overexpressed COX-2, IL-1β and -6 in response to pro-inflammatory stimuli (Croxtall et al, 2003;Damazo et al, 2006;Hannon et al, 2003;Yang et al, 2006;Yona et al, 2004;Yona et al, 2005), suggesting that AnxA1 is an endogenous inhibitor of inflammatory responses .…”
Section: A Clarkmentioning
confidence: 99%